A comprehensive review of cycloastragenol: Biological activity, mechanism of action and structural modifications - Mengting He; Ke Wang; Haojie Che; Huifang Wang; Kan Yang; Guiming Zhang; Jingchun Yao; Jinxin Wang (Elsevier, 2022)
Cycloastragenol (CAG) is a sapogenin of Astragaloside IV (AG-IV), isolated from the dried roots of legumes Astragalus mongolica or Astragalus membranaceus. Cycloastragenol has a steroidal skeleton of tetracyclic triterpene and possess diverse pharmacological activities such as anti-aging, anti-inflammatory, anti-fibrosis, pro-wound healing, liver protection and endothelial protection. In addition, cycloastragenol is the only telomerase activator reported in natural products, which is closely related to MAPK and PI3K/Akt signaling pathways. This review provides a theoretical basis for the development of cycloastragenol into the candidate for the treatment of multi-factorial diseases in clinic, focusing on the extensively biological activities as well as the mechanism of action and structural modification and aiming to attract researchers to conduct in-depth studies on cycloastragenol. Meanwhile, the pharmacokinetics and toxicology studies of CAG are also described for further druggability exploration to provides valuable reference.